Structure Semantics Action Verbs Related to Feet in Sasak Language Menu Meni Dialect: Metalanguage Studies Semantics Experience - Zulkarnaen, Zulkarnaen; Rajeg, I Made; Sri Satyawati, Made Sri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
Research This discuss structure semantics verb action related to language feet Sasak  menu dialect meni . Purpose from study this , namely discuss classification verb action related to language feet Sasak and mapping structure semantics verb action related to language feet Sasak . Research This use theory Metalanguage Semantics Natural ( Weirbicka , 1996) and theory Classification Verbs ( Givon , 1984) in analyze data. Researchers use method qualitative with collect data using method see and method Proficient , analyzing data using method match referential as well as formal and informal presentation of data . Research results This show that There are 27 variations lexicon Language Sasak related to feet from 16 question list use Indonesian and grouped into two kinds verb that is process verbs and verbs action . Structure semantics verb action related to mapped feet become 27 meanings original and classified to in meaning  polysemy incomposition with various type meaning  in accordance with use verb the .